Pengaruh Sistem Digital terhadap Kinerja Karyawan di Kampus Politeknik LP3I Makkassar - Sudirman, Sudirman; Larafista, Jihan; Rahmi, Rahmi; Maryam, Maryam (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
As technology develops increasingly rapidly, gradually some jobs that can only be done by humans are starting to be replaced by technology that is becoming more sophisticated year by year. This is an era where work patterns are no longer carried out traditionally, but have entered the modern/digital era. Where workers must be able to adapt the process so that they can keep up with current developments and be able to compete in this digital era. The phenomenon in this research is the existence of dynamics with digital systems. This type of research is quantitative research using descriptive methods. The data processed is primary data obtained from the results of distributing questionnaires using saturated sampling techniques. Of the 25 employees who were all respondents. Data analysis was carried out using the SPSS Version 25 program. The research results show that there is a positive influence of digital systems on employee performance.